Functional Expression and Peroxisomal Targeting of Rat Urate Oxidase in Monkey Kidney Cells - Yeldandi, Anjana V. (Gene Expr, 2018)
Humans and hominoid primates lack the enzyme urate oxidase, which catalyzes the oxidation of uric acid to allantoin. In rats and most other mammals, urate oxidase is present as a crystalloid core within the peroxisomes of liver parenchymal cells. To determine whether functionally active recombinantly expressed urate oxidase can be targeted to the peroxisome as well as display the crystalloid core-like structure, we expressed rat urate oxidase cDNA in African green monkey kidney cells (CV-1 cells) under the control of a cytomegalovirus promoter. Cell lines stably expressing urate oxidase were isolated. Northern blot analysis revealed a 1.3-kb transcript and immunoblot analysis confirmed the presence of urate oxidase in the stably transfected cells. The recombinant urate oxidase expressed in CV-1 cells was functionally active. Immunofluorescence microscopy revealed that the expressed protein was visualized as discrete granules in the cytoplasm. Electron microscopy and immunocytochemical localization studies showed that the recombinantly expressed protein formed distinct crystalloid core structures with bundles of tubules within single membrane limited cytoplasmic organelles. On cross section, the recombinant urate oxidase tubular structures are arranged as circles of 10 surrounding a slightly larger circle. This arrangement is reminiscent of urate oxidase-containing cores in rat liver peroxisomes. Immunocytochemical studies confirmed that the recombinantly expressed urate oxidase is correctly targeted to the catalase-containing peroxisomes in these CV-1 cells.